Keefektifan Penerapan Model SEQIP Dalam Pembelajaran Konsep Dasar IPA Di PGSD FKIP UNEJ - Imam Mudakir, (Pendidikan Dasar, 2005)
Tujuan penelitian ini adalah untuk mengetahui tingkat keefektifan penerapan model SEQIP dalam pembelajaran konsep dasar IPA. Percobaan dilakukan pada kelas yang dipilih secara purposive random. Data diperoleh dari pre-test dan past-test dan dianalisis dengan rumus keefektifan relatif. Hasilnya menunjukan cukup efektif (28,2%).This research aims at finding out the effectiveness of the application of SEQIP model in learning basic concept of Natural Science. The data obtained were the results of pre-test and post-test given to selected students of D2 PGSD and analyzed using relative effectiveness. The finding shows that SEQIP was quite effective, therefore it is suggested that teachers and related institutions use SEQIP learning model to teach Basic concept of Natural Science.